Panglima Laot (Adat Pribumisasi Islam sebagai Upaya Resolusi Konflik Kelautan di Kuala Langsa Aceh) - Febriandi, Yogi (LoroNG: Media Pengkajian Sosial Budaya, 2015)
This article discusses the negotiation between Islam and Indigenous rite among the fishermen community in Kuala Langsa, Aceh, in managing marine resources and the social life of fishermen. Employing the theory of Dahrendorf, the author analyzed the conflict in fishermen community from the perspective of social class analysis. The data were collected through in-depth interview and observation of daily behavior of fishermen communities from March to May 2015. The author showed that the conflict in fishermen community of Kuala Langsa were mostly caused due to the limitation of struggle for the area and means of production. For example, the conflict between those fishermen who use Pukat Langgar (traditional fishing tecnic) and those who employ Pukat Harimau (trawl) and also the resistance over indigenous regulations. Nevertheless, by using religion as a means that is associated with local custom and tradition, this paper found that Islamized indigenous tradition of Panglima Laot has become the strategic social element that is able to construe the seeds of conflict and opaque among the fishermen community of Kuala Langsa. Tulisan ini membahas negosiasi antara Islam dan Adat pada masyarakat Nelayan di Kuala Langsa, Aceh, dalam mengelola sumber daya kelautan dan kehidupan sosial nelayan.Menggunakan teori Dahrendorf, penulis menganalisis konflik pada masyarakat nelayan dari perspektif analisis kelas sosial.Sumber data dikumpulkan melalui wawancara mendalam dan observasi perilaku keseharian masyarakat nelayan selama bulan Maret hingga Mei 2015.Penulis memperlihatkan bahwa konflik yang terjadi pada masyarakat Nelayan Kuala Langsa lebih dikarenakan adanya pembatasan ataupun perebutan arena dan alat produksi nelayan.Sebagai contoh konflik antara nelayan pukat langgar dan pukat harimau dan juga perlawanan terhadap beberapa peraturan adat yang dijalankan.Namun, dengan menggunakan agama sebagai alat yang disatukan dengan kehidupan tradisi dan kebiasaan setempat, tulisan ini memperlihatkan bahwa AdatPanglima Laotmenjadi elemen sosial yang sangat setrategis dalam mengurai benih-benih maupun konflik yang terjadi pada masyarakat nelayan Kuala Langsa.